Science Communication as Knowledge Transfer Infrastructure in the Knowledge-Based Economy - Eclarin, Eigram Alexandria G. (Journal of Research in Vocational Education, 2025)
This paper examines the evolution of science communication as a foundational element of the knowledge - based economy, highlighting its transformation from philosophical dialogues to structured knowledge transfer systems. Emphasizing nuclear and photonic domains, it illustrates how communication practices have mirrored societal and economic needs through historical stages such as natural philosophy, popularization of science, and science PR. The study argues that knowledge transfer represents the most advanced form of science communication, particularly under cognitive and semiotic frameworks. By mapping these changes and analyzing historical examples, the paper offers a compelling narrative of how science communication now plays a central role in national development and public engagement. This paper aims to trace science communication’s historical evolution and current role of science communication as a vehicle for knowledge transfer within the Knowledge - based Economy. The article is part of an extensive scientific research focus on Risk Communication in Nuclear and Photonic Fields in the Knowledge - based Economy.